Study of convergence using residual links in various or combinations of different DNN - Fang, Wen Jie (Nanyang Technological University, 2020)
Residual Network (ResNet) has gained considerable amount of attention in recent years as it has not only solve the optimisation problem in very deep network through the use of skip connections, it has also achieved state-of-the-art performance on ImageNet classification challenge.